Targeting Inflammatory Pathways by Triterpenoids for Prevention and Treatment of Cancer - Yadav, Vivek R. (MDPI, 2010)
Traditional medicine and diet has served mankind through the ages for prevention and treatment of most chronic diseases. Mounting evidence suggests that chronic inflammation mediates most chronic diseases, including cancer. More than other transcription factors, nuclear factor-kappaB (NF-κB) and STAT3 have emerged as major regulators of inflammation, cellular transformation, and tumor cell survival, proliferation, invasion, angiogenesis, and metastasis. Thus, agents that can inhibit NF-κB and STAT3 activation pathways have the potential to both prevent and treat cancer. In this review, we examine the potential of one group of compounds called triterpenes, derived from traditional medicine and diet for their ability to suppress inflammatory pathways linked to tumorigenesis. These triterpenes include avicins, betulinic acid, boswellic acid, celastrol, diosgenin, madecassic acid, maslinic acid, momordin, saikosaponins, platycodon, pristimerin, ursolic acid, and withanolide. This review thus supports the famous adage of Hippocrates, “Let food be thy medicine and medicine be thy food”.